1995
DOI: 10.1007/bf00011791
|View full text |Cite
|
Sign up to set email alerts
|

Activity of nitrifying populations in grassland soil polluted by polychlorinated biphenyls (PCBs)

Abstract: The activity of nitrification was studied in the period of 1992 -1994 in two grassland plots from the surroundings of a municipal waste incinerator. The soil parameters were fully comparable in both plots and the soils differed in the level of polychlorinated biphenyls (PCBs). The concentration of PCBs found in Klajdovka -control plot (KL):-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The toxic effect of PCBs in soil could be due to oxidation products that could occur particularly in mixtures formed during incineration of various materials containing PCBs [15]. In three year study, Dusek and Tesarová [10] observed significant decline in MB-C content and respiration activity in soil contaminated only by 14.4 ng-g" 1 PCBs originated from municipal waste incinerator. From that viewpoint, it appears to be important that the lowest stability of microbial biomass and mineralization capability were detected in the soil T contaminated by mixture with the highest I-TEQ (2378-TCDD) for PCBs congeners (8.4 pg-g" 1 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The toxic effect of PCBs in soil could be due to oxidation products that could occur particularly in mixtures formed during incineration of various materials containing PCBs [15]. In three year study, Dusek and Tesarová [10] observed significant decline in MB-C content and respiration activity in soil contaminated only by 14.4 ng-g" 1 PCBs originated from municipal waste incinerator. From that viewpoint, it appears to be important that the lowest stability of microbial biomass and mineralization capability were detected in the soil T contaminated by mixture with the highest I-TEQ (2378-TCDD) for PCBs congeners (8.4 pg-g" 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…Laboratory incubations of soil samples were arranged according to Dusek and Tesafová [10]. Composite soil samples (10 g per one replicate) were amended with 2 ml of glucose water solution provided saturating amount of glucose: 5000 ug C g" 1 dry soil (0.5%).…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…Dusek (1995) in experiments with increasing dozes of РСРs found a strong decrease of the nitrite-oxidizing bacteria.…”
Section: The Impact Of the Main Soil Pollutants On Soil Microfloramentioning
confidence: 89%
“…For nitrification, which is the second step in the mineralization of nitrogen from organic matter, so far studies of the effects on metals of this process have not produced a consistent picture. Dusek [82] found that Cd disrupted nitrification in spiked soils; however, high concentrations (100 and 500 mg Cd kg À1 ) were required, suggesting that the function had low sensitivity. Murray et al [83], in contrast, found no effect of Cd, Cu, Ni and Pb, while Kandeler et al [84] found that nitrification was influenced more by the supply of organic substrate in sludge than by the heavy metal content.…”
Section: Populations and Communitiesmentioning
confidence: 99%